ความตระหนักรู้ต่อการเตรียมรับมือกับเหตุการณ์แผ่นดินไหวในผู้ที่อาศัยในอาคารสูงในกรุงเทพมหานคร - ศุภกร ตุลย์ไตรรัตน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purpose of this cross-sectional descriptive study was to examine the earthquake literacy among people who live in high rise building in Bangkok. The sample of this study consisted of 482 people that were selected by stratified random sampling method. A self-administered questionnaire were collected from July to September 2017. Response rate was 82.99%. The result of this study showed that most of the sample were female. Median of age is 29 years old. Ninety-five point five percent of the sample had never experienced with earthquake before. Workplace never provided any earthquake drill 88.75 %. Eighty-nine point two five percent of the sample estimated that they are unprepared. Thirty-six point seven five percent of sample had earthquake literacy in average level. Relative factors that affect literacy includes residents who are widowed, divorced, and separated, live in high rise buildings between the 8th-14th floor, work in 15th-21st story office buildings, their estimating score of earthquake preparation and score of response knowledge during and after an earthquake. Most of sample had earthquake literacy in average level. However, most of the sample estimated that they are unprepared. Therefore, it should be considered to promote prevention such as provide an earthquake education to raise literacy of earthquake preparation to reduce the loss.